Moving from gender policies to gender equality in the South Asian energy sector - Shakya, Shristi; Durga, Neha; Alvi, Muzna; Singh, Tushar; Ringler, Claudia (CGIAR System Organization, 2023)
Across South Asia, gender equality and social inclusion (GESI) are widely acknowledged as vital pillars of a just transition to renewable energy. So why do men continue to make most decisions regarding energy use? This was the conundrum grappled with by the latest NEXUS Gains webinar, Gender and Energy: Measures to accelerate equity and social inclusion in South Asia’s rural energy transition.